2020
DOI: 10.13057/biodiv/d211038
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and antioxidants responses of dairy cow fed with a combination of feed and duckweed (Lemna minor) as a mixture for improving milk biosynthesis

Abstract: Abstract. Tanuwiria UH, Mushawwir A. 2020. Hematological and antioxidants responses of dairy cows fed with a combination of feed and duckweed (Lemna minor) as a mixture for improving performance. Biodiversitas 21: 4741-4746. A total of twenty-five, 5-7th-lactation-old or 7-8thyears-old dairy cows were used in the current study to study the effect of feed duckweed (Lemna minor) on the hematological status and parameters related antioxidant in the dairy cow. Each group of treatment involved 5 replicates with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Based on this research, the triglyceride profile of Sentul Chickens in the starter phase without irradiated chitosan was the highest compared to the treatment given irradiated chitosan, while in NEFA Sentul chickens for starter phase without irradiated chitosan were the lowest compared to treatments given irradiated chitosan. Furthermore, in association with the research reported [21,22], chitosan supplementation significantly increased the rate of lipolysis, reduced the rate of adipocyte hypertrophy, triglyceride accumulation, and activity of lipoprotein in adipose tissue of the epididymis, also decreased the activity of liver enzymes [24] related to lipid biosynthesis [25]. Chitosan supplementation has been reported to activate phosphorylated adenosine monophosphate (AMP) significantly-activated protein kinase (AMPK) [26,27], and a high-fat diet induces the expression of lipogenic transcription factors (Peroxisome Proliferator-Activated Receptor Gamma/PPAR-γ and sterol receptor element-binding protein 1c/ SREBP1c) [28] in the liver and adipose tissue -29,30].…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Based on this research, the triglyceride profile of Sentul Chickens in the starter phase without irradiated chitosan was the highest compared to the treatment given irradiated chitosan, while in NEFA Sentul chickens for starter phase without irradiated chitosan were the lowest compared to treatments given irradiated chitosan. Furthermore, in association with the research reported [21,22], chitosan supplementation significantly increased the rate of lipolysis, reduced the rate of adipocyte hypertrophy, triglyceride accumulation, and activity of lipoprotein in adipose tissue of the epididymis, also decreased the activity of liver enzymes [24] related to lipid biosynthesis [25]. Chitosan supplementation has been reported to activate phosphorylated adenosine monophosphate (AMP) significantly-activated protein kinase (AMPK) [26,27], and a high-fat diet induces the expression of lipogenic transcription factors (Peroxisome Proliferator-Activated Receptor Gamma/PPAR-γ and sterol receptor element-binding protein 1c/ SREBP1c) [28] in the liver and adipose tissue -29,30].…”
Section: Resultssupporting
confidence: 54%
“…The results of previous research showed that chitosan is a cationic polyelectrolyte that acts as an amino substitute to interact with proteins. In addition, chitosan has a positive ionic charge that chemically provides the ability to bind to negative charges, namely fat [36,37,38,39], cholesterol, protein, and macromolecules, and this can affect the growth of the chicken body weight [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…Related the importance of glycogen breakdown, it has also been published by previous researchers that glycogen as an energy reserve (Mushawwir et al, 2010(Mushawwir et al, , 2018Loyau et al, 2014;Jiwandini et al, 2020;Mushawwir et al, 2020d), in the form of polysaccharides (Siskos et al, 2017;|Tanuwiria et al, 2020), is broken down through the phosphorylation mechanism (Xu et al, 2015;Tian et al, 2015;Slimen et al, 2016) by activating chemical signals through the AMP cycle (Gray et 2015;Roland et al, 2016;Sang-Ho et al, 2018), guanylyl cyclase as a fist messenger (Pickler et al, 2013;Carrol et al, 2016;Nurmalia et al, 2020;Mushawwir et al, 2021b). This overhaul mechanism is needed to be able to meet the energy requirements for the homeostasis process in a state of reduced feed consumption (Renaudeau et al, 2012;Ammer et al, 2018;Suwarno et al, 2019;Mushawwir et al, 2020c).…”
Section: Resultsmentioning
confidence: 93%
“…One of the strategies adopted to reduce the impact of heat stress is the provision of natural feed additives, namely diallyn n-sulphide (Dn-S) from garlic (garlik). Dn-S is an volatile component that has reactive oxygen (O) and sulfur (S) atoms to be able to bind to free radicals (Tian et al, 2015, Tanuwiria et al, 2020Mushawwir et al, 2021c). It is hoped that with its reaction ability, it is able to prevent the bad effects of free radicals in lowering the metabolic rate.…”
Section: Introductionmentioning
confidence: 99%
“…Although the research on the average levels of SGPT and SGOT has not been determined, when compared with purebred chickens, the results obtained are still classified as average levels for both. It is stated that low levels of SGPT and SGOT show that the liver cells were not damaged [21][22][23]. Impaired liver function results from damage to hepatocytes which causes changes in transport function and membrane permeability, leading to the release of SGPT, SGOT, and -GT enzymes in the cytoplasm into blood circulation [24].…”
Section: Resultsmentioning
confidence: 99%